Investigating the structural morphology, linear/nonlinear optical characteristics of Nd2O3 doped PVA polymeric composite films: Kramers-Kroning approach. (7th October 2021) - AlAbdulaal, T H; Ali, H Elhosiny; Ganesh, V; Aboraia, A M; Khairy, Yasmin; Hegazy, H H; Soldatov, V Alexander V; Zahran, H Y; Abdel-Wahab, Mohamed Shaaban; Yahia, I S
Abstract: This research presents a novel optical polymer of polyvinyl alcohol (PVA), as a host matrix, doped with various weight concentrations of Neodymium oxides (Nd2 O3 ) metals, as a filler, where Nd2 O3 /PVA polymeric thin films were synthesized to be successfully utilized as a dynamic media for polymeric lasers. The solution casting method, simple and low-cost, was applied to homogeneously prepared composite films of Nd2 O3 -doped PVA. The crystallinity of the structures, the uniformity of the films, and the interactions among the Nd2 O3 doping metals and the PVA matrix were approved via x-ray diffraction (XRD) and scanning electron microscopy (SEM) analysis. The remarkable effects of various weight concentrations of Nd2 O3 doping on the optical parameters for Nd2 O3 /PVA composite polymeric thin films were determined using a UV–vis spectrophotometer. Kramers-Kroning's approach was exploited to evaluate the linear refractive index ( n ), energy bandgap ( E g ), and nonlinear optical effects for the proposed polymers. Moreover, a manual Z-scan method was applied to study the optical limiting effects using red He-Ne laser and green diode laser. This study illustrated some advantages of the outcome of the semi-crystalline structure, amazing linear optical parameters, including low optical energy bandgaps, brilliant dielectric constant, substantial optical limiting, as well as excellent nonlinear optical parameters of the proposed Nd2 O3 /PVA nanocomposite films. Thus, it is possible to conclude that the synthesized Nd2 O3 /PVA polymeric films play central roles in different promising, practical optoelectronic applications, such as lasers, optical filters, optical communication, light-emitting diodes, and optical switching.